Penta-Graphene as a Potential Gas Sensor for NO x Detection - Meng-Qi Cheng; Qing Chen; Ke Yang; Wei-Qing Huang; Wang-Yu Hu; Gui-Fang Huang (Nanoscale Research Letters, 2019)
Abstract Two-dimensional (2D) penta-graphene (PG) with unique properties that can even outperform graphene is attracting extensive attention because of its promising application in nanoelectronics. Herein, we investigate the electronic and transport properties of monolayer PG with typical small gas molecules, such as CO, CO2, NH3, NO and NO2, to explore the sensing capabilities of this monolayer by using first-principles and non-equilibrium Green’s function (NEGF) calculations. The optimal position and mode of adsorbed molecules are determined, and the important role of charge transfer in adsorption stability and the influence of chemical bond formation on the electronic structure of the adsorption system are explored. It is demonstrated that monolayer PG is most preferred for the NO x (x = 1, 2) molecules with suitable adsorption strength and apparent charge transfer. Moreover, the current−voltage (I−V) curves of PG display a tremendous reduction of 88% (90%) in current after NO2 (NO) adsorption. The superior sensing performance of PG rivals or even surpasses that of other 2D materials such as graphene and phosphorene. Such ultrahigh sensitivity and selectivity to nitrogen oxides make PG a superior gas sensor that promises wide-ranging applications.